The Digitization of Madrasah Administration: Relationship between Transformational Leadership and Technology Implementation in Jambi - Tabroni Tabroni; A A Musyaffa Musyaffa (AL-ISHLAH: Jurnal Pendidikan, 2025)
The digital transformation of school administration is increasingly essential in ensuring efficiency and transparency in education. In the context of Islamic elementary schools (Madrasah Ibtidaiyah) in Jambi City, this study investigates the role of transformational leadership in facilitating the implementation of administrative digitalization. A mixed-methods approach was employed, combining quantitative and qualitative data collection. Surveys and interviews were conducted with 39 school principals, and the quantitative data were analyzed using Pearson correlation and regression analysis, while qualitative data were interpreted through thematic analysis based on Miles and Huberman's framework. The findings indicate that digital platforms such as EMIS, SIMPATIKA, and digital archiving tools have enhanced administrative performance in terms of data management, reporting, and transparency. However, implementation remains uneven due to disparities in infrastructure and digital literacy. Quantitative analysis revealed a strong and significant positive correlation between transformational leadership and the success of digital administration (r = 0.894, p 0.01), with leadership accounting for approximately 89% of the variance. Principals demonstrating idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration were more effective in promoting innovation and organizational adaptability. The study highlights that transformational leadership is a key driver of digital innovation in Islamic education settings. It fosters a culture of collaboration, professional development, and readiness for change. To support sustainable digital transformation in madrasahs, leadership development, targeted digital training for staff, and policy alignment are essential. These findings contribute to leadership theory and practice in Islamic educational administration.